The biomedical engineer’s pledge: overview and context - Antoni Ivorra; Txetxu Ausín; Laura Becerra-Fajardo; Antonio J. del Ama; Jesús Minguillón; Aracelys García-Moreno; Jordi Aguiló; Filipe Oliveira Barroso; Bart Bijnens; Oscar Camara; Sara Capdevila; Roger Castellanos Fernandez; et al. (Medical & Biological Engineering & Computing, 2026)
Although biomedical engineering (BME) is a profession with ethical responsibilities comparable to those in medicine, it has, until now, lacked a counterpart to the Hippocratic Oath. While professional societies have established codes of ethics for biomedical engineers, these documents lack the symbolic and ceremonial significance of an oath or pledge. By contrast, the recitation of the Hippocratic Oath, or its modern version, the “Physician’s Pledge,” serves as a powerful rite of passage for medical students, fostering a strong sense of ethical duty at the start of their professional journey. However, the content of the Hippocratic Oath includes elements specific to clinical practice and is not directly applicable to biomedical engineering. To fill this gap, we have created a “Biomedical Engineer’s Pledge,” comprising a preamble, ten promises, and a concluding statement, to inspire ethical awareness and establish a meaningful graduation tradition. Graphical abstract

Corrigendum to ‘A horizon scan exercise for aquatic invasive alien species in Iberian inland waters’ Sci. Total Environ.869 (2023) 161798 - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

A horizon scan exercise for aquatic invasive alien species in Iberian inland waters - Francisco J. Oficialdegui; José M. Zamora-Marín; Simone Guareschi; Pedro M. Anastácio; Pablo García-Murillo; Filipe Ribeiro; Rafael Miranda; Fernando Cobo; Belinda Gallardo; Emili García-Berthou; Dani Boix; Andrés Arias; et al. (Science of The Total Environment, 2023)

Killer whales of the Strait of Gibraltar, an endangered subpopulation showing a disruptive behavior - Ruth Esteban; Alfredo López; Álvaro Garcia de los Rios; Marisa Ferreira; Francisco Martinho; Paula Méndez‐Fernandeza; Ezequiel Andréu; José C. García‐Gómez; Liliana Olaya‐Ponzone; Rocío Espada‐Ruiz; Francisco J. Gil‐Vera; Cristina Martín Bernal; et al. (Marine Mammal Science, 2022)

Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Simonetta Fraschetti; Chris McOwen; Loredana Papa; Nadia Papadopoulou; Meri Bilan; Christoffer Boström; Pol Capdevila; Marina Carreiro-Silva; Laura Carugati; Emma Cebrian; Marta Coll; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.

Clinical implications of intratumor heterogeneity: challenges and opportunities - Santiago Ramón y Cajal; Marta Sesé; Claudia Capdevila; Trond Aasen; Leticia De Mattos-Arruda; Salvador J. Diaz-Cano; Javier Hernández-Losa; Josep Castellví (Journal of Molecular Medicine, 2020)
In this review, we highlight the role of intratumoral heterogeneity, focusing on the clinical and biological ramifications this phenomenon poses. Intratumoral heterogeneity arises through complex genetic, epigenetic, and protein modifications that drive phenotypic selection in response to environmental pressures. Functionally, heterogeneity provides tumors with significant adaptability. This ranges from mutual beneficial cooperation between cells, which nurture features such as growth and metastasis, to the narrow escape and survival of clonal cell populations that have adapted to thrive under specific conditions such as hypoxia or chemotherapy. These dynamic intercellular interplays are guided by a Darwinian selection landscape between clonal tumor cell populations and the tumor microenvironment. Understanding the involved drivers and functional consequences of such tumor heterogeneity is challenging but also promises to provide novel insight needed to confront the problem of therapeutic resistance in tumors.

Health-related quality of life in well-differentiated metastatic gastroenteropancreatic neuroendocrine tumors - P. Jiménez-Fonseca; A. Carmona-Bayonas; E. Martín-Pérez; G. Crespo; R. Serrano; M. Llanos; C. Villabona; R. García-Carbonero; J. Aller; J. Capdevila; E. Grande (Cancer and Metastasis Reviews, 2015)

Molecular biology of neuroendocrine tumors: from pathways to biomarkers and targets - J. Capdevila; A. Meeker; R. García-Carbonero; K. Pietras; A. Astudillo; O. Casanovas; A. Scarpa (Cancer and Metastasis Reviews, 2014)

Analysis of genes involved in 6-deoxyhexose biosynthesis and transfer in Saccharopolyspora erythraea - M. Doumith; P. Weingarten; U. F. Wehmeier; K. Salah-Bey; B. Benhamou; C. Capdevila; J.-M. Michel; W. Piepersberg; M.-C. Raynal (Molecular Genetics and Genomics, 2000)

Differences between lactate concentration of samples from ear lobe and the finger tip - J. Feliu; J. L. Ventura; R. Segura; G. Rodas; J. Riera; A. Estruch; A. Zamora; L. Capdevila (Journal of Physiology and Biochemistry, 1999)